2007
DOI: 10.1038/nrmicro1643
|View full text |Cite
|
Sign up to set email alerts
|

The role of ecological theory in microbial ecology

Abstract: Microbial ecology is currently undergoing a revolution, with repercussions spreading throughout microbiology, ecology and ecosystem science. The rapid accumulation of molecular data is uncovering vast diversity, abundant uncultivated microbial groups and novel microbial functions. This accumulation of data requires the application of theory to provide organization, structure, mechanistic insight and, ultimately, predictive power that is of practical value, but the application of theory in microbial ecology is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
673
1
15

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 851 publications
(712 citation statements)
references
References 62 publications
10
673
1
15
Order By: Relevance
“…Microbial ecology has shown that many mechanisms controlling metazoans apply similarly to microorganisms [18]. This study contributes to this literature with an example of positive density dependence.…”
Section: Discussionmentioning
confidence: 70%
“…Microbial ecology has shown that many mechanisms controlling metazoans apply similarly to microorganisms [18]. This study contributes to this literature with an example of positive density dependence.…”
Section: Discussionmentioning
confidence: 70%
“…Positive species-energy relationships have been investigated at the field and lab scales (Srivastava and Lawton, 1998;Hurlbert, 2006). However, the species-energy theory has largely been examined from an macroecological framework and remains nascent within microbial ecology as a discipline; but see discussions by Prosser et al, 2007. An exception to this has been presented in a study focused on the energy-diversity relationships in arctic seafloor microbial ecosystems (Bienhold et al, 2012).…”
Section: Diversity-productivity Relationshipsmentioning
confidence: 99%
“…Notwithstanding the importance of soil microbial processes at all scales, the observations of these processes in their spatial context is hindered by soil opacity, the complex pore spaces, and variations in properties across scales from pores to aggregates, pedon, and field. Additionally, the lack of quantitative ecological models hinders effective application of experimental methods for systematic hypothesis testing, generalization, and organization of experimental information [Prosser et al, 2007;O'Donnell et al, 2007;Faust and Raes, 2012].…”
Section: Introductionmentioning
confidence: 99%